PEMBERIAN AIR KELAPA SEBAGAI ZAT PENGATUR TUMBUH ALAMI PADA STUM MATA TIDUR BEBERAPA KLON TANAMAN KARET (Hevea brasiliensisMuell Arg.) - Syarifah Ulya Muazzinah; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed to determine the effect of the concentration of coconut water as a natural plant growth regulators in accelerating growth and getting the best concentration on growth of rubber budded stump for several clones. This research conducted  experiments using a completely randomized design (CRD) with 2 factors. The first factor is the clones (K) consisting of three clones, namely PB 260, GT 1 and IRR 39. The second factor is the concentration of coconut water (A), which consists of four levels is without the application of coconut water, coconut water concentration of 25%, 50% and 75%. Data were analyzed using analysis of variance and Duncan's multiple range test at 5% level. The results showed that the main factor clones and provision of coconut water concentration significantly affected to parameters grow buds, plant height, stem diameter, but does not affect to number of leaves of rubber budded stump. There is interaction between clones with the application of coconut water concentration to parameter grow buds, but do not interact on other parameters. Rubber clones PB 260 and GT 1 have the better growth than rubber clone IRR 39. Application of coconut water concentration of 50% and 75% on PB 260 and GT 1, and the application of coconut water concentration of 25% and 50% on IRR 39 hadbetter in increasing the time of grow buds, plant height, stem diameter and number of leaves of rubber budded stump. Keywords:Coconut water, buddedstump, rubber clones, Growth